Enhanced piezocatalytic therapy of MRSA-infected osteomyelitis using ultrasound-triggered copper nanocrystals-doped barium titanate - Yang Wu; Bei Chen; Xia Chen; Guoqiang Zhu; Wei Du; Liming Qing; Panfeng Wu; Zhenxing Wang; Juyu Tang; Hui Xie (Bioactive Materials)
Osteomyelitis caused by methicillin-resistant Staphylococcus aureus (MRSA) biofilms poses a major therapeutic challenge due to persistent infection and bone loss. Optimizing anti-infection and promoting bone repair are the main goals to improve the efficiency of osteomyelitis treatment. Herein, we present an ultrasound (US)-actived Cu-BTO@Gua composite piezoelectric sonosensitizer, created by conjugating guanidine (Gua) groups, a component that permeates the biofilm matrix, onto US-absorbing Cu-doped barium titanate (BTO). The guanidine groups demonstrate strong affinity for matrices abundant in negatively charged components, facilitating deeper biofilm penetration. Cu doping not only amplifies the piezoelectric effect, but also introduces abundant oxygen vacancies to suppress electron-hole pair recombination. Under US irradiation, the nanocomposite catalyzes the substrate to produce toxic ROS in the acidic infection microenvironment, while Cu depletes glutathione to aggravate oxidative stress, leading to bacterial toxin inactivation, biofilm disintegration, and bacterial death. Additionally, Cu-BTO@Gua promotes the polarization of M1 macrophages to the M2 phenotype by inhibiting nuclear factor-κB, which subsequently activates the transforming growth factor β (TGF-β) signaling pathway to support osteogenesis. This dual-action approach offers a promising strategy for improving clinical outcomes of complex bone infections.